Neuroscience and Cognitive Psychology Insights into the Classical Theological Debate about Free Will and Responsibility - Mattei, Tobias Alecio (Christian scholar's review, 2013)
In recent years significant advances have occurred in both fields of neuroscience and cognitive psychology which have provided further comprehension regarding the biological structures underlying intentionality and decision making. In this essay, Tobias A. Mattei reviews the insights such empirical data might provide to the classical theological debate about human will and responsibility. After analyzing the positions of John Calvin, Jonathan Edwards, Martin Luther, and the Westminster Confession of Faith, Mattei exposes how all of them involved a view of human will as “self-determined” and “corrupted.” His discussion then considers how empirical data strongly supports the view of “free will” as a complex and elaborated “illusion” of human mind. Such findings are in agreement with the previously discussed reformed perspective of a compatibilistic view of human will, which is essentially deterministic, but not reducible to the biochemical and neurophysiological levels.